Kompetencje pracowników źródłem sukcesu podmiotów leczniczych: Employee competence as a source of medicinal agents’ success - Rasińska, Renata; Nowakowska, Iwona (Management and Administration Journal, 2021)
The knowledge and competence of employees are seen as valuable components of a human capital of an organization and therefore, obtaining the ability for proper management of workers’ competencies is an important task for managers in the case of medicinal agents. Elements conducive to success are: continuous company development, resources, processes and environment. In the case of medicinal agents attention should be drawn to the benefits aimed at employees (the possibility of creating a harmonious team) or customers (customer satisfaction, the ability to satisfy their needs). Intangible assets are as important as the material and human resources and, in this case, they are the key to success. Also very important is the motivating role of competition, as well as searching for the possibility to establish partnerships. The creation of a good trusted team is, for many companies, a measure of success. The work should encourage employees to develop, and thus more and more specialists who are interested in the development of organization and their employees indicate the needs of constantly raising qualification. The development of employee resources is implemented by various forms of training that expand knowledge, skills and shape the behaviuor of employees, as well as planning and realization of individual professional careers. The promotion of an active attitude towards training is crucial in the process of popularizing programmes of employee management.